2018
DOI: 10.1155/2018/3179207
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Work Zone Collision Probabilities via Clustering: Application in Optimal Deployment of Highway Response Teams

Abstract: This paper proposes a clustering approach to predict the probability of a collision occurring in the proximity of planned road maintenance operations (i.e., work zones). The proposed method is applied to over 54,000 short-term work zones in the state of Maryland and demonstrates an ability to predict work zone collision probabilities. One of the key applications of this work is using the predicted probabilities at the operational level to help allocate highway response teams. To this end, a two-stage stochasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Other studies employed clustering analysis for roadway crashes and safety projects [43][44][45]. Similarly, Sekuła et al [46] proposed a clustering approach to predict the probability of a collision occurring in the proximity of planned road maintenance operations (i.e., work zones). Different other studies also concluded data mining techniques are more advanced and better than traditional statistical techniques [47][48][49][50][51].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies employed clustering analysis for roadway crashes and safety projects [43][44][45]. Similarly, Sekuła et al [46] proposed a clustering approach to predict the probability of a collision occurring in the proximity of planned road maintenance operations (i.e., work zones). Different other studies also concluded data mining techniques are more advanced and better than traditional statistical techniques [47][48][49][50][51].…”
Section: Literature Reviewmentioning
confidence: 99%